An investigation of autonomic arousal and attentional mechanisms in children with ADHD and Autism - Bellato, Alessio (2020)
The present doctoral project was aimed at investigating the impact of Attention Deficit Hyperactivity Disorder (ADHD) and Autism Spectrum Disorder (ASD) on measures of physiological arousal, alerting/vigilance, attention orienting and executive functions. 106 children between 7 and 15 years of age (31 typically developing; 24 ADHD-only; 18 ASD-only; 33 ADHD&ASD) performed a battery of eye-tracking and EEG experimental paradigms, while parent-reported measures were used to evaluate the severity of symptoms of ASD, ADHD and other psychiatric conditions.